Fortress Europe? Challenges and Failures of Migration and Asylum Policies - Jünemann, Annette; Scherer, Nikolas; Fromm, Nicolas (Springer Fachmedien Wiesbaden : Imprint: Springer VS, 2017)
VII, 188 p. 6 illus. in color.